2016
DOI: 10.18632/oncotarget.8469
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the transcriptional profile of the Mediator complex across human cancer types

Abstract: The Mediator complex is a key regulator of gene transcription and several studies demonstrated altered expressions of particular subunits in diverse human diseases, especially cancer. However a systematic study deciphering the transcriptional expression of the Mediator across different cancer entities is still lacking.We therefore performed a comprehensive in silico cancer vs. benign analysis of the Mediator complex subunits (MEDs) for 20 tumor entities using Oncomine datasets. The transcriptional expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
(56 reference statements)
0
27
0
Order By: Relevance
“…Recently, an increasing number of Mediator complex subunits have been identified as relevant components in a range of human diseases including different cancer entities (3,4,7). To foster the knowledge of Mediator complex biology in human cancers and to evaluate its complex and potentially entity-specific subunit composition, we performed a pan-cancer analysis of Mediator complex transcriptome profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an increasing number of Mediator complex subunits have been identified as relevant components in a range of human diseases including different cancer entities (3,4,7). To foster the knowledge of Mediator complex biology in human cancers and to evaluate its complex and potentially entity-specific subunit composition, we performed a pan-cancer analysis of Mediator complex transcriptome profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several subunits have been implicated in a growing number of human diseases including developmental disorders (3,6) and cancer (4,7). Most evidence has been gathered for the kinase module subunit CDK8, which has been linked to colon and pancreatic cancer (8,9) and was also investigated as a potential target in cancer therapy (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…By integrating and transmitting diverse regulative signals, for example, from transcription factors to RNA Polymerase II, Mediator complex function may impact almost all cellular processes . Numerous studies reported aberrant activities of distinct Mediator subunits contributing to the pathogenesis of diverse disorders including cancer . Several genes encoding Mediator subunits are affected by chromosomal aberrations or gene mutations in cancer cells and certain subunits affect cancer‐related pathways by specific molecular interference .…”
Section: Introductionmentioning
confidence: 99%
“…2 Numerous studies reported aberrant activities of distinct Mediator subunits contributing to the pathogenesis of diverse disorders including cancer. [3][4][5] Several genes encoding Mediator subunits are affected by chromosomal aberrations 6,7 or gene mutations [8][9][10] in cancer cells and certain subunits affect cancerrelated pathways by specific molecular interference. 11,12 Therefore, particular subunits have been implied to define certain molecular cancer subtypes and serve as therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical staining was conducted on TMAs using the Ventana Benchmark automated staining system (Ventana Medical System, Tuscon, AZ, USA) as described previously (7, 9, 18, 19). In brief, slides were incubated at room temperature with the primary antibody: anti-TRAP220/MED1 rabbit polyclonal (dilution 1:500, ab64965, lot number: GR54026, Abcam).…”
Section: Methodsmentioning
confidence: 99%